Striking dual functionality of a novel Pd@Eu-MOF nanocatalyst in C(sp2)–C(sp2) bond-forming and CO2 fixation reactions. Issue 19 (29th April 2020) - You, Li-Xin; Yao, Shan-Xin; Zhao, Bai-Bei; Xiong, Gang; Dragutan, Ileana; Dragutan, Valerian; Liu, Xue-Gui; Ding, Fu; Sun, Ya-Guang
Abstract : A Pd@Eu-MOF nanocatalyst was obtained via solution impregnation and H2 reduction and used in recyclable Suzuki–Miyaura reactions and in the chemical fixation of CO2 with epoxides. Abstract : Pd nanoparticles were immobilized on a highly porous, hydrothermally stable Eu-MOF via solution impregnation and H2 reduction to yield a novel Pd@Eu-MOF nanocatalyst. This composite was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), inductively coupled plasma optical emission spectroscopy (ICP-OES), powder X-ray diffraction (PXRD) and X-ray photoelectron spectroscopy (XPS). Unprecedentedly, the Pd@Eu-MOF nanocatalyst could be applied with excellent results in two strikingly different, mechanistically distinct, reactions i.e., Suzuki–Miyaura cross-coupling and cycloaddition of CO2 to a range of epoxides. Under the best reaction conditions, 98–99% yields have been attained in both catalytic processes. Moreover, in either case the heterogeneous catalyst was easily recovered and efficiently reused for more than four cycles, indicating its high stability and reproducibility. PXRD, TEM and XPS measurements on the recycled catalyst confirmed that it maintained its original structure and morphology; no Pd NP agglomeration was observed.